STRATEGI PENINGKATAN KEMAMPUAN LEMBAGA EKONOMI PADA KAWASAN HORTIKULTURA UNGGULAN DI KABUPATEN JEMBER - Aryo Fajar Sunartomo (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2014)
Horticulture are now seeded Jember government is durian, orange, mangosteen, corn, watermelon, etc. This commodity is technically feasible to be developed, in terms of economic benefit and socially acceptable to the local community. But in fact in the field of commodity value in the form of price and productivity are still low. This is due to the marketing of these commodities is still traditional, the lack of touch technology infrastructure both on farm and off farm causing farmers to become weak bargaining position. people is likely to deceive the people. In the future development of the agricultural sector is still encountered some obstacles, particularly in the development of farming systems based agribusiness and agro-industries. Location of the study determined (purposive) in Jember is the region / district that has the potential to be developed as a superior horticultural commodities. The form to be used in this study is a descriptive case study strategy. Results indicate that the fulfillment of the financing needs of farmers farming done creatively by combining source - a source of financing that can be reached like banks, cooperatives, traders or the relatives/friends. SWOT analysis results show the value of IFAS and EFAS 2,65 to 2,40, which means having a prospective opportunity to develop and possess the competence to do it. Keywords: agribusiness, horticulture, development strategy